Methoxycarbonyl trifluoromethyl disulfide, CH3OC(O)SSCF 3: Synthesis, structure and conformational properties - Torrico Vallejos, Sonia (2010)
Pure methoxycarbonyl trifluoromethyl disulfide, CH3OC(O) SSCF3, has been prepared quantitatively by the reaction of CH 3OC(O)SCl and Hg(SCF3)2. The conformational properties of the novel molecule have been studied by vibrational spectroscopy [IR(gas) and Raman(liquid)] and quantum chemical calculations (B3LYP and MP2 methods). The gaseous compound exhibits a conformational equilibrium at room temperature where the most stable form has C1 symmetry with a synperiplanar (syn) orientation of the CO double bond with respect to the S-S disulfide bond. A second form is observed in the gaseous IR spectra corresponding to a conformer with the carbonyl bond CO in antiperiplanar (anti) position with respect to the S-S single bond. The structure of a single crystal of CH3OC(O)SSCF3 has been determined by X-ray diffraction analysis at low temperature using a miniature zone melting procedure. The crystalline solid (triclinic, P1, a = 6.4698(5) Å, b = 9.0499(8) Å, c = 12.5700(11) Å, α = 97.219(6)°, β = 93.131(5)°, γ = 96.888(5)°and Z = 4) consists exclusively of molecules with the synperiplanar conformation and the usual gauche orientation around the disulfide bond [(CS-SC) = 91.06(15)°] is adopted. The geometrical parameters agree with those obtained from quantum chemical calculations. © 2010 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.